Characterization of the ospZ Promoter in Shigella flexneri and Its Regulation by VirB and H-NS - Basta, David W. (American Society for Microbiology, 2013)
OspZ is an effector protein of the type III secretion system in Shigella spp. that downregulates the human inflammatory response during bacterial infection. The ospZ gene is located on the large virulence plasmid of Shigella. Many genes on this plasmid are transcriptionally repressed by the nucleoid structuring protein H-NS and derepressed by VirB, a DNA-binding protein that displays homology to the plasmid partitioning proteins ParB and SopB. In this study, we characterized the ospZ promoter and investigated its regulation by H-NS and VirB in Shigella flexneri. We show that H-NS represses and VirB partially derepresses the ospZ promoter. H-NS-mediated repression requires sequences located between −731 and −412 relative to the beginning of the ospZ gene. Notably, the VirB-dependent derepression of ospZ requires the same VirB binding sites as are required for the VirB-dependent derepression of the divergent icsP gene. These sites are centered 425 bp upstream of the ospZ gene but over 1 kb upstream of the icsP transcription start site. Although these VirB binding sites lie closer to ospZ than icsP, the VirB-dependent increase in ospZ promoter activity is lower than that observed at the icsP promoter. This indicates that the proximity of VirB binding sites to Shigella promoters does not necessarily correlate with the level of VirB-dependent derepression. These findings have implications for virulence gene regulation in Shigella and other pathogens that control gene expression using mechanisms of transcriptional repression and derepression.